Preservice teachers' motivation profiles, self-regulation, and affective outcomes in online learning. Issue 1 (2nd January 2021) - Cho, Moon-Heum; Cheon, Jongpil; Lim, Seongmi
ABSTRACT: The purpose of this study was to examine the relationship between motivation profiles and self-regulation in online students and self-regulation as a predictor of affective learning outcomes, depending on students' motivation profiles. A total of 556 online preservice teachers participated in this study at a university in the United States of America. Cluster analyses yielded three subgroups of motivation: high, average, and low. One-way multivariate analysis of variance revealed that the degree of student self-regulation differed, depending on motivation profiles. In addition, multiple regression showed that for students with high motivation profiles, self-regulation between student and content and between student and instructor related with their affective learning outcomes, but only self-regulation between student and instructor related with affective learning outcomes for students with average and low motivation profiles. Overall, study results revealed that motivation profiles related with the online students' self-regulation and with their affective learning outcomes as well.